Mast cells: key players in digestive system tumors and their interactions with immune cells - Feihong Shu; Jie Yu; Youjia Liu; Fang Wang; Guoyou Gou; Min Wen; Chen Luo; Xianmin Lu; Yanxia Hu; Qian Du; Jingyu Xu; Rui Xie (Cell Death Discovery)
Abstract Mast cells (MCs) are critical components of both innate and adaptive immune processes. They play a significant role in protecting human health and in the pathophysiology of various illnesses, including allergies, cardiovascular diseases and autoimmune diseases. Recent studies in tumor-related research have demonstrated that mast cells exert a substantial influence on tumor cell behavior and the tumor microenvironment, exhibiting both pro- and anti-tumor effects. Specifically, mast cells not only secrete mediators related to pro-tumor function such as trypsin-like enzymes, chymotrypsin, vascular endothelial cell growth factor and histamine, but also mediators related to anti-tumor progression such as cystatin C and IL-17F. This dual role of mast cells renders them an under-recognized but very promising target for tumor immunotherapy. Digestive system tumors, characterized by high morbidity and associated mortality rates globally, are increasingly recognized as a significant healthcare burden. This paper examines the influence of mast cell-derived mediators on the development of tumors in the digestive system. It also explores the prognostic significance of mast cells in patients with various gastrointestinal cancers at different stages of the disease. Additionally, the article investigates the interactions between mast cells and immune cells, as well as the potential relationships among intratumoral bacteria, immune cells, and mast cell within digestive system microenvironment. The aim is to propose new strategies for the immunotherapy of digestive system tumors by targeting mast cells.